2011
DOI: 10.1111/j.1532-950x.2011.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Screw‐In Femoral Implant in Cementless Total Hip System

Abstract: Helica femoral prosthesis alters strain distribution in the proximal aspect of the femur and exhibits initial micromotion. Failure load in axial compression of the Helica-implanted femur is less than that of the normal femur, but greater than that expected in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 32 publications
1
35
1
Order By: Relevance
“…Bone medial surface strain in this study and a recent Helica study revealed significantly different results after prosthesis implantation. Medial strain data for intact femora are comparable between studies (−570 µstrain in the current study vs. −800 µstrain in the study by Kim et al); however, medial strain becomes much less compressive (−190 µstrain) using the traditional technique in the previous study compared to greater compressive strain using both the traditional and modified techniques in the current study (−700 and −790 µstrain, respectively). There are several possible reasons for greater compressive medial strain after implantation in the current study—most notably implant size selection and surgical procedure.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Bone medial surface strain in this study and a recent Helica study revealed significantly different results after prosthesis implantation. Medial strain data for intact femora are comparable between studies (−570 µstrain in the current study vs. −800 µstrain in the study by Kim et al); however, medial strain becomes much less compressive (−190 µstrain) using the traditional technique in the previous study compared to greater compressive strain using both the traditional and modified techniques in the current study (−700 and −790 µstrain, respectively). There are several possible reasons for greater compressive medial strain after implantation in the current study—most notably implant size selection and surgical procedure.…”
Section: Discussioncontrasting
confidence: 62%
“…Total hip replacement (THR) for treatment of coxofemoral osteoarthritis secondary to canine hip dysplasia, traumatic osteoarthritis, coxofemoral luxation, avascular necrosis of the femoral head, and failed femoral head and neck excision has been evolving in veterinary medicine since the 1970s . Despite great therapeutic potential, complications with varying degrees of clinical importance occur with cemented and cementless fixation systems.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…achieve short-term stability by various methods depending on the implant system used (press-fit, locking screw fixation, or screw-in implants) and long-term stability via bone in-growth (on-growth) into implants. [5][6][7] The Zurich Cementless THR (Kyon, Zurich, Switzerland) was developed at the University of Zurich in the late 1990s 6 (Fig. 1).…”
Section: Key Pointsmentioning
confidence: 99%